RETINOPATHY IN A CASE OF FAMILIAL HYPERCHOLESTEROLEMIA WITH DIABETES- A RARE CASE REPORT. - sahu, Pallavi priyadarsani; Dr. Soumya Kanta Mohanty; Das, Manmath Kumar (Student’s Journal of Health Research Africa, 2024)
Background Familial hyperlipidemia is a genetic disorder characterized by high levels of LDL cholesterol and is associated with an increased risk of sudden cardiac death. However, the majority of cases of familial hypercholesterolemia remain undiagnosed or diagnosed at a later stage. Hyperlipidemia per se plays a major role in the pathophysiology of diabetes and its complications. Lipid-lowering agents have a protective effect on the progression of diabetic retinopathy and reduce the risk of diabetic macular oedema. Hence in cases of familial hypercholesterolemia with diabetic retinopathy a combined and aggressive approach is vital for better visual outcome. Case presentation In this report, an unusual case of 54 years old male presented to the ophthalmology OPD of Kalinga Institute of Medical Sciences, Bhubaneswar with diabetic retinopathy which was unresponsive to conventional treatment. Upon thorough evaluation, he was diagnosed with a case of familial hypercholesterolemia, and lipid-lowering therapy was initiated along with intravitreal anti-VEGF injections to which he responded better and there was a significant improvement in visual acuity. Conclusion This case report emphasizes that all cases of diabetic retinopathy unresponsive to treatment should be thoroughly evaluated. Familial hypercholesterolemia is a grave disease with serious implications. Early diagnosis and timely intervention play a crucial role in improving visual prognosis and life expectancy in such patients.